Determinación de un quiver Grassmanniano isomorfo a una curva proyectiva plana - Urtecho Vidaurre, Carlos Raúl (2021)
The present research work was carried out in order to determine a quiver Grassmanian_x000D_ isomorphic to a given projective plane curve. For this, the projective space was pre sented, on which the Zariski topology was defined, which allowed us to introduce the_x000D_ morphisms and isomorphisms between projective varieties. After realized the quiver_x000D_ Grasssmannian as a projective variety, it was shown that every projective variety is_x000D_ isomorphic to a quiver Grassmannian. Thus, particularly, given a projective plane cur ve, there is a quiver such that the quiver Grassmannian constructed from this quiver_x000D_ is isomorphic to the projective plane curve given